1975
DOI: 10.1055/s-0028-1090433
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Neurinomas. — A comprehensive clinical and statistical study on 47 cases

Abstract: Based on an unselected material forty-seven cases of intraspinal neurinomas treated in a period of seven years, this report presents a comprehensive, clinical and statistical analysis. Divergences from the literature in respect of case history, distribution and frequency are pointed out. Attention is paid to the difficulties of early diagnosis. Problems of surgical treatment and the importance of microsurgical dissection are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
1
2

Year Published

1978
1978
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 1 publication
0
19
1
2
Order By: Relevance
“…Hori et al (8) reported that 71.1% of their 45 spinal neuromas (including seven neurofibromas) originated from sensory roots, 17.8% from the motor roots, and 11.1% from both roots. Most spinal neuromas (which included not only schwannomas but also neurofibromas in some reports) are entirely intradural: 66 to 74% are intradural, 15 to 23% dumbbell (intradural-extradural), and 2 to 15% are extradural (8,15,16,18). Although the cervical (8), thoracic (15), or lumbar predilection of spinal neuromas has been mentioned (18), neuromas of the first two cervical nerve roots are uncommon, accounting for only 5.3% of all spinal neuromas and 18% of cervical neuromas (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hori et al (8) reported that 71.1% of their 45 spinal neuromas (including seven neurofibromas) originated from sensory roots, 17.8% from the motor roots, and 11.1% from both roots. Most spinal neuromas (which included not only schwannomas but also neurofibromas in some reports) are entirely intradural: 66 to 74% are intradural, 15 to 23% dumbbell (intradural-extradural), and 2 to 15% are extradural (8,15,16,18). Although the cervical (8), thoracic (15), or lumbar predilection of spinal neuromas has been mentioned (18), neuromas of the first two cervical nerve roots are uncommon, accounting for only 5.3% of all spinal neuromas and 18% of cervical neuromas (2).…”
Section: Discussionmentioning
confidence: 99%
“…Most spinal neuromas (which included not only schwannomas but also neurofibromas in some reports) are entirely intradural: 66 to 74% are intradural, 15 to 23% dumbbell (intradural-extradural), and 2 to 15% are extradural (8,15,16,18). Although the cervical (8), thoracic (15), or lumbar predilection of spinal neuromas has been mentioned (18), neuromas of the first two cervical nerve roots are uncommon, accounting for only 5.3% of all spinal neuromas and 18% of cervical neuromas (2). George and Lot (2) reported 44 C2 neuromas (including neurofibromas) in 42 patients with C1 and C2 neuromas, in whom 16 lesions were entirely extradural, 19 were of the dumbbell type, and 7 were strictly intradural.…”
Section: Discussionmentioning
confidence: 99%
“…40) The median age at diagnosis of neurofibroma is similar in patients with NF1 and without NF1, although both groups are younger than patients with spinal schwannomas, whose median age at presentation is in the fifth decade. 32) The sex distribution is equal in all. 23) The rarity of pelvic neurofibroma, even in association with NF1, may be due to the silent nature of these tumors, as there is usually very little neurological deficit.…”
Section: Discussionmentioning
confidence: 99%
“…time before diagnosis 3 . The benign nature of ordinary spinal schwannomas is well documented [4][5][6][7] . Total surgical removal can usually be achieved and shortterm outcome is favorable in those who are not too severely crippled before operation 5,7 .…”
mentioning
confidence: 99%